To determine who is correct about the solution sets of the equations, we will solve each equation step-by-step.
Equation A:
\( 3(4 - 5h) - 7 = -12 + 2h \)
Expanding and simplifying the left side:
- Distributing: \( 34 - 35h - 7 = 12 - 15h - 7 = 5 - 15h \)
- Setting the equation: \( 5 - 15h = -12 + 2h \)
Bringing all terms involving \( h \) to one side and constants to the other:
- \( 5 + 12 = 15h + 2h \)
- \( 17 = 17h \)
- \( h = 1 \)
Equation B:
\( 2(p - 3) - 1 = \frac{6p + 14}{2} \)
Start by simplifying the left side:
- \( 2p - 6 - 1 = 2p - 7 \)
- Setting the equation: \( 2p - 7 = \frac{6p + 14}{2} \)
Multiply both sides by 2 to eliminate the fraction:
- \( 2(2p - 7) = 6p + 14 \)
- \( 4p - 14 = 6p + 14 \)
Rearranging gives:
- \( 4p - 6p = 14 + 14 \)
- \( -2p = 28 \)
- \( p = -14 \)
Equation C:
\( \frac{2}{3}v - 3 + \frac{8}{3} = -1 \)
First, combine constants on the left side:
- \( -3 + \frac{8}{3} = -\frac{9}{3} + \frac{8}{3} = -\frac{1}{3} \)
- So the equation is: \( \frac{2}{3}v - \frac{1}{3} = -1 \)
Adding \( \frac{1}{3} \) to both sides:
- \( \frac{2}{3}v = -1 + \frac{1}{3} = -\frac{3}{3} + \frac{1}{3} = -\frac{2}{3} \)
Solving for \( v \):
- \( v = -\frac{2}{3} \div \frac{2}{3} = -1 \)
Summary of Solutions:
- Equation A: \( h = 1 \)
- Equation B: \( p = -14 \)
- Equation C: \( v = -1 \)
Conclusion:
- Tamara claims Equations A and C have the same solution: False (1 vs -1).
- Payton claims Equations B and C have the same solution: False (-14 vs -1).
- Krish claims all three equations have the same solution: False.
- Haruki claims none of the equations have the same solution: True.
Thus, the correct answer is:
B) Haruki.